ANALISIS DETERMINAN IMPOR BAWANG MERAH DI INDONESIA PERIODE 2002-2018 - I.K.G. Bendesa, Lilis Hendri Purwanti (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The purpose of this research is to partially analyze the effect of exchange rate, production, land area, consumption and price on imported shallots in Indonesia. Analyzing the role of prices, in moderating the effect of consumption on imported shallots in Indonesia. The analysis was carried out using multiple linear regression and moderation, using secondary data for the period 2002-2018 sourced from the Indonesian Central Statistics Agency, the Ministry of Agriculture, and Bank Indonesia. The analysis shows that partially the exchange rate variable has a negative and significant effect on the import of shallots in Indonesia, the production variable has a negative and significant effect on the import of shallots in Indonesia, the land area variable has a positive and significant effect on shallots imports in Indonesia, the consumption variable has a positive effect insignificant towards the import of shallots on the import of shallots in Indonesia and the variable price (moderation) weakens the effect of consumption on shallots imports in Indonesia for the period 2002-2018. Keywords: imports, shallots, exchange rates, production, land area, consumption, prices.